2020
DOI: 10.3389/fendo.2020.00411
|View full text |Cite
|
Sign up to set email alerts
|

A Novel E2F1-EP300-VMP1 Pathway Mediates Gemcitabine-Induced Autophagy in Pancreatic Cancer Cells Carrying Oncogenic KRAS

Abstract: Autophagy is an evolutionarily preserved degradation process of cytoplasmic cellular constituents, which participates in cell response to disease. We previously characterized VMP1 (Vacuole Membrane Protein 1) as an essential autophagy related protein that mediates autophagy in pancreatic diseases. We also demonstrated that VMP1-mediated autophagy is induced by HIF-1A (hypoxia inducible factor 1 subunit alpha) in colon-cancer tumor cell lines, conferring resistance to photodynamic treatment. Here we identify a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 68 publications
(84 reference statements)
1
24
0
Order By: Relevance
“…This plasmid loses the green color at acidic pH, which makes a sophisticated marker of mitochondrial input to the autolysosome, that is, a good marker of mitophagy ( Kim et al, 2013 ). (e) GFP-sh-VMP1 plasmid for VMP1 down-regulation designed by Ropolo et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…This plasmid loses the green color at acidic pH, which makes a sophisticated marker of mitochondrial input to the autolysosome, that is, a good marker of mitophagy ( Kim et al, 2013 ). (e) GFP-sh-VMP1 plasmid for VMP1 down-regulation designed by Ropolo et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is an evolutionarily preserved degradation process of cytoplasmic cellular constituents, associated with cell response to stresses such as hypoxia in cancer microenvironment [ 97 ]. As a key component and a marker of autophagy, LC3 expression in PC tissue significantly correlates with a poor outcome [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histone acetyltransferase E1A-binding protein p300 (EP300) is a ubiquitously expressed pleiotropic multidomain coactivator that catalyzes acetylation of histone and nonhistone proteins [22]. EP300 mutations contribute to an unfavorable phenotype in a number of solid tumors and hematological malignancies and therefore EP300 is often considered as tumor promoter [23]. Pathological studies have shown that EP300 was highly expressed in many tumors.…”
Section: Discussionmentioning
confidence: 99%